(untitled) (Ameghiniana, 2014)
A new species of Cardiatheriinae rodents, Procardiatherium rosendoi, is presented in this paper. This species comes from the continental deposits from Belen, Catamarca. Due to the morpho structural features of those cheek teeth which appeared better preserved (p4 and mr), this species is considered as a transitional evolutionary stage between the already know species of Procardiatherium and Kiyutherium. The prevailing environmental conditions and the probable age of the bearing sediments are herein discussed.